An ecologically sound HPLC determination of LEVOMENOL in topical therapies using a certified reference material with green properties - Jin-Kui Ma; Ahmed S. Darwish; Amer Al Ali; Aaser M. Abdelazim; Wageh Sobhy Darwish; Xiang Li; Xiao-Chen Huang (Results in Chemistry)
The development of suitable stability-indicating research in pharmaceutical analysis has received a lot of attention lately. A stability-indicating RP-HPLC method was developed and validated to identify chamomile extract as levomenol in topical cream formulations using an approved reference material. Levomenol was exposed to a variety of drastic conditions in accordance with the ICH standards. Levomenol and its degradants were separated using the gradient LC technique; levomenol was measured at 40 °C on a Hypersil C-18 column. The usage of this traditional and common column and mobile phase emphasizes the economical, low cost by avoiding specific rare analysis requirements. Acetonitrile and 0.005 M potassium dihydrogen phosphate buffer pH 2.6 are combined in different ratios to form the mobile phase at a flow rate of 1.2 mL/min. Levomenol was detected at 204 nm, and the detected values are ranging from 1.0 to 10.0 μg/mL. The total injection time was <30 min, suggesting that the LC analysis is suitable for routine medication quality control assessments. For the best separation, acetonitrile was required. To assess the sustainability impact, three different methods were used: the MoGAPI, the AES, and AGREE. The chromatographic process's environmental friendliness is demonstrated by the final AES measurement of 67.5, AGREE measurement of 0.62, MoGAPI measurement of 70 with five green sections, BAGI score of 75.0, and whiteness measurement of 97.9. Needless to say, the simultaneous process is robust, long-lasting, accurate, precise, and good for the environment. The advantages and whiteness of the proposed strategy were compared to those of the published one. Lastly, levomenol may be sufficiently evaluated for routine quality control in both its pure form and the topical cream dosage form that contains chamomile extract. Moreover, the uniqueness of the suggested technique is guaranteed owing to its whiteness score and simplicity regarding the utilized techniques against the published HPLC methods discussed below.